2008
DOI: 10.1159/000127972
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Disease-Modifying Therapies in Relapsing Remitting Multiple Sclerosis: A Systematic Comparison

Abstract: The treatment of relapsing-remitting multiple sclerosis (RRMS) has become more effective over the last decade with the advent of the currently available disease-modifying therapies (DMTs). Pivotal clinical studies differ in many characteristics, such that cross-comparisons of relative risk reductions are of limited value and can be misleading. Our objective was to compare the clinical efficacy of currently approved first-line DMTs in patients with RRMS, applying an evidence-based medicine approach. We reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…An early systematic review comparing placebo controlled, double blind clinical trials concluded that all three INF-ß agents demonstrate equivalent efficacy between low and high dose interferon treatments [1]. However, in the recent systematic reviews of placebo controlled trials conducted by Freedman et al [2] and Goodin [3] both concluded that high dose interferon treatment had superior effectiveness on MRI and relapse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…An early systematic review comparing placebo controlled, double blind clinical trials concluded that all three INF-ß agents demonstrate equivalent efficacy between low and high dose interferon treatments [1]. However, in the recent systematic reviews of placebo controlled trials conducted by Freedman et al [2] and Goodin [3] both concluded that high dose interferon treatment had superior effectiveness on MRI and relapse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Various disease-modifying drugs, including IFNb-1a and IFNb-1b, glatiramer acetate, natalizumab, mitoxantrone, and fingolimod that are licensed worldwide to reduce the frequency of clinical attacks with the expectation of slowing disability progression [14]. Great majority of studies related to IFNs have been directed towards to determination of their effects on diseases and biological structures [9,39].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective currently available treatment is natalizumab, a humanized monoclonal antibody against CD49d/very late antigen-4 (VLA-4), which is generally also well tolerated, but has led to progressive multifocal leukoencephalopathy (PML), an opportunistic and often fatal infection of the brain by the polyoma virus JC, in over 300 patients so far. A chemotherapeutic agent, mitoxantrone, is used as second-line therapy for more severe RRMS and also for SPMS [5]. Mitoxantrone can only be given for a very limited period of time due to its cardiac toxicity, and secondary leukemias have occurred in up to 2.…”
Section: Ms Treatment Landscapementioning
confidence: 99%